O desenvolvimento da empatia em um grupo de trabalhadoras na perspectiva teórico-metodológica da clínica psicodinâmica do trabalho - Kuhn, Marisa Canello (2017)
Empathy is considered an ability that benefits social and professional relationships and should be promoted in the organizational context through reliable methods. This study aimed to verify the validity of the intervention, in the theoretical-methodological perspective of the Psychodynamic Work Clinic, for the development of empathy in the inter-relational process in work groups. It is an action research - an uncontrolled intervention study, called "before and after", with an experimental group of 65 workers, cleaning assistants, between 22 and 64 years old, from 13 units of a Higher Education Institution (HEI). The intervention in the theoretical and methodological perspective of the Psychodynamic Work Clinic, which prioritizes the speech and listening of the workers, occurred in 09 groups of 06 to 12 members, in twelve fortnightly meetings, one hour each, in the premises of the HEI, in the period from March to August 2016. In addition to a pre-intervention socio-demographic questionnaire and registration protocols of the meetings, which were developed during the intervention process, the Palografic test and the Social Skills Inventory (IHS) were used, administered pre- and postintervention. Speech analysis was used in the collection and analysis of the protocols. The analysis of the palographic and IHS instruments was performed using the non-parametric QuiQuadrado and McNemar statistical tests at the 5% level of significance. The protocols analysis results indicated improvement in the quality of interrelationships, decrease of conflicts, and increase of the participants empathy level. In comparison between the pre and post intervention results, there were favorable changes in the general results of the Palographic test, regarding social and affective contact (p = 0.0080) and the desire for closeness to others (p = 0.0104) and IHS Total score, which balances resources and social skills deficits (0.0237). In the individual analysis of the two items evaluated in the Palographic test, there was a very significant reduction in the variables related to the reserve attitude (p = 0.0001) and the relationships instability (p = 0.0197); And there was a very significant increase in the variables related to the ease of adaptation (p = 0.0001), and balanced interpersonal relationship (p = 0.0147). In the factorial scores of the IHS, there were significant changes in factor 1 - coping and self-assertion with risk, with a very elaborated repertoire increase (p = 0.0 084) and a decrease in the inferior repertoire (p = 0.0040). Also in factor 3, with a significant increase in the very elaborate repertoire (p = 0.0093) and a decrease in the lower repertoire (p = 0.0005). The results showed that there were significant positive changes in the interpersonal relationships among the participants of this group, indicating an increase in the empathy between them. The intervention from the perspective of the Psychodynamic Work Clinic method proved to be valid in this process of change. The present research highlights the importance of promoting the development of empathic skills in the context of work, through the intervention based on the Psychodynamic Work Clinic method, in order to provide better interaction and interpersonal relationship, as well as to favor teamwork and minimize conflicts.